2017
DOI: 10.1155/2017/3681989
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Readability Analysis of Online Patient Education Resources on Inflammatory Bowel Diseases

Abstract: a readability grade level of less than 7th grade for patient directed information. In this study, we use validated readability metrics to analyze patient information from prominent websites pertaining to ulcerative colitis and Crohn's disease. Methods. The terms "Crohn's Disease," "Ulcerative Colitis," and "Inflammatory Bowel Disease" were queried on Google and Bing. Websites containing patient education material were saved as a text file and then modified through expungement of medical terminology that was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…While there have been assessments of the quality of websites on many key areas of health care, such as diabetes [23], obesity [24], and hypertension [25], and on surgical interventions [26,27], there is a dearth of assessment about the quality of web-based information pertaining to medications. Such assessments are necessary to inform clinicians of the quality of content likely to be accessed by their patients, who are particularly interested in the likelihood and nature of adverse side effects.…”
Section: Internet Standardsmentioning
confidence: 99%
“…While there have been assessments of the quality of websites on many key areas of health care, such as diabetes [23], obesity [24], and hypertension [25], and on surgical interventions [26,27], there is a dearth of assessment about the quality of web-based information pertaining to medications. Such assessments are necessary to inform clinicians of the quality of content likely to be accessed by their patients, who are particularly interested in the likelihood and nature of adverse side effects.…”
Section: Internet Standardsmentioning
confidence: 99%
“…Many studies have demonstrated that patient materials are often written above the American Medical Association and National Institutes of Health recommendation of 6th grade reading level. [6][7][8][9][10][11][12] Ensuring that materials are readable is an essential first step, especially because more than one-third of Americans have basic or below basic literacy. 13 However, reading grade level alone does not capture if materials are accessible to patients.…”
mentioning
confidence: 99%
“…Literacy is measured by the Flesch reading ease score and the Flesch-Kinkaid grade level (FGL). A low Flesch reading ease score (FRE) of less than 60 and an FGL greater than 7 indicate that the MIS was too difficult for the average adult [4].…”
mentioning
confidence: 99%